2020
DOI: 10.1016/j.drugalcdep.2020.108080
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with skin and soft tissue infections among people who inject drugs in the United Kingdom: A comparative examination of data from two surveys

Abstract: Background: People who inject drugs (PWID) are at high risk of injection-related skin and soft tissue infections (SSTI). If not treated promptly, these can lead to serious health complications, which are a considerable healthcare burden. Data from two community surveys, with different approaches, were used to assess SSTI prevalence and associated factors among PWID to inform intervention implementation. Methods: Data were analysed from two surveys, a national surveillance survey (n=2,874; 2017-18) of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…The survey sample comprised 455 people with a history of injecting drug use. Demographics align with characteristics of PWID recorded in national surveillance data ( Doran et al, 2020 ); predominately male (75%, n = 341), of White ethnicity (74%, n = 336) and a mean age of 46 years. The primary drug injected was heroin, either alone (44%, n = 199) or in combination with crack cocaine (49%, n = 255).…”
Section: Participants: Ssti Risk and Demographic Contextsupporting
confidence: 59%
See 1 more Smart Citation
“…The survey sample comprised 455 people with a history of injecting drug use. Demographics align with characteristics of PWID recorded in national surveillance data ( Doran et al, 2020 ); predominately male (75%, n = 341), of White ethnicity (74%, n = 336) and a mean age of 46 years. The primary drug injected was heroin, either alone (44%, n = 199) or in combination with crack cocaine (49%, n = 255).…”
Section: Participants: Ssti Risk and Demographic Contextsupporting
confidence: 59%
“…This paper draws on mixed method data generated for the Care & Prevent study with 455 PWID, many of whom report rough sleeping and injecting-related hospitalisation, to explore the dynamics of medical care seeking and avoidance among the most marginalised. Sample demographics are comparable to those of PWID represented in UK surveillance data ( Doran et al, 2020 ). Findings presented focus on qualitative accounts, from a subsample of survey participants, to illustrate both the severity of health harms incorporated into daily lives and the structures that inform care delay.…”
Section: Introductionmentioning
confidence: 78%
“…Analysis has demonstrated that C&P sample is comparable to those of PWID participating in the larger National UAM surveillance survey [32]. We have some confidence, therefore, that findings reported in this paper are generalisable to the broader population of PWID in the UK [33]…”
Section: Strengths and Weaknessessupporting
confidence: 55%
“…Early detection of COVID-19 could help mitigate possible complications caused by the virus among PWUD, who may have underlying chronic medical conditions that increase their risk of developing severe COVID-19 illness, such as COPD, asthma, cardiovascular diseases, and viral hepatitis [ 9 ]. PWUD are at risk for sepsis and endocarditis, and commonly have skin and soft tissue infections [ 34 , 35 ] which, when left untreated, can lead to hospitalisation and even amputation, putting them at greater risk if infected with COVID-19.…”
Section: Discussionmentioning
confidence: 99%